Anti-symmetrical curved composite laminate subject to delamination induced by thermal cycling - Treml, A. E.; Gouvêa, R. F.; Sales, R. C.M.; Donadon, M. V.; Shiino, M. Y. [UNESP]; Bressan, J. D. (Wiley, 2017)
Composite structures usually undergo to temperature variations in aircraft during landing/taking off and when cruising at high altitude. Under these conditions and in combination with curved structures, they can generate severe thermal stresses that induce delaminations. Considering the importance of studying delamination in these conditions, this research imposed an anti-symmetrical laminate to cyclic temperature variations of 130 °C and −70 °C with the objective of inducing varied curvatures and, consequently, crack growth. Different from standardized test procedures, this test setup elastically deformed coupons without external forces and forward experimentally and numerically evaluated the strain energy release rate (SERR) during crack propagation. This procedure enabled the assessment of delamination rate (da/dN) as a function of maximum SERR. The experimental results were compared with numerical results obtained by ABAQUS Finite Element code. Despite large scatter in experimental results, a reasonable correlation between experimental and numerical results was obtained in terms of crack growth rate (da/dN) as a function of the maximum SERR.
Keywords: carbon/epoxy laminates; composite materials; fracture mechanics; thermal fatigue